2001
DOI: 10.1136/jnnp.70.3.305
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory ECG and analysis of heart rate variability in Parkinson's disease

Abstract: Objectives-Cardiovascular reflex tests have shown both sympathetic and parasympathetic failure in Parkinson's disease. These tests, however, describe the autonomic responses during a restricted time period and have great individual variability, providing a limited view of the autonomic cardiac control mechanisms. Thus, they do not reflect tonic autonomic regulation. The aim was to examine tonic autonomic cardiovascular regulation in untreated patients with Parkinson's disease. Methods-24 Hour ambulatory ECG wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
117
3
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(142 citation statements)
references
References 42 publications
15
117
3
5
Order By: Relevance
“…In keeping with such an inability to shift the cardiac sympathovagal balance toward a sympathetic predominance, the increase of the LF/HF ratio during tilt was reduced in PD compared with control subjects, similarly to PDOH subjects. A dynamic impairment of cardiac sympathetic modulation in accordance with our results has already been described by power spectrum analysis of RR variability during 24-hour ECG recordings 34 and the tilt maneuver. 10 In the PD group, despite the absence of orthostatic hypotension, the tilt-induced increase of LF SAP was blunted compared with control subjects, similar to PDOH subjects.…”
Section: Cardiovascular and Autonomic Changes Induced By A Gravitatiosupporting
confidence: 77%
See 1 more Smart Citation
“…In keeping with such an inability to shift the cardiac sympathovagal balance toward a sympathetic predominance, the increase of the LF/HF ratio during tilt was reduced in PD compared with control subjects, similarly to PDOH subjects. A dynamic impairment of cardiac sympathetic modulation in accordance with our results has already been described by power spectrum analysis of RR variability during 24-hour ECG recordings 34 and the tilt maneuver. 10 In the PD group, despite the absence of orthostatic hypotension, the tilt-induced increase of LF SAP was blunted compared with control subjects, similar to PDOH subjects.…”
Section: Cardiovascular and Autonomic Changes Induced By A Gravitatiosupporting
confidence: 77%
“…34 Finally, immunohistochemical staining of postmortem specimens of cardiac tissue showed a decreased number of sympathetic axons innervating the left anterior ventricular wall of the heart of 4 patients suffering from Parkinson's disease. 15 Based on cardiac norepinephrine spillover, 18 immunohistochemical staining 15 methodologies, and the presence of Lewy bodies in ganglionic cells and axons of the paravertebral sympathetic chain, 35 the concomitant presence of a peripheral sympathetic denervation disease has been hypothesized recently in Parkinson's disease.…”
Section: Cardiovascular and Autonomic Profile Of Parkinson's Disease mentioning
confidence: 99%
“…To the best of our knowledge, prior studies have focused on group comparisons ,ofter reaching contradictory results [1,3,16,20,21,25,28,29,32,33,35]. It should be noted that, even if a significant statistical difference associated to a certain feature is consistently revealed across several studies, this is not sufficient to demonstrate its potential application to the clinical necessity of single-subject characterization.…”
Section: Discussionmentioning
confidence: 80%
“…According to the study by Haapaniemi et al [16], when analyzing 24h ECG recordings all HRV spectral components were found to be significantly lower in PD patients when compared to controls [16]. In another study, which evaluated 10 consecutive minutes of resting ECG recordings, HRV High Frequency (HF) power (thought to mainly reflect parasympathetic activity)…”
Section: Introductionmentioning
confidence: 99%
“…8 The variation of heart rate with respiration is known as sinus arrhythmia. 12,14,15 Inspiration increases and expiration decreases the heart rate.…”
Section: Important Tests Used For Evaluation Of Autonomic Functionsmentioning
confidence: 99%